2009
DOI: 10.1017/s1355770x08005007
|View full text |Cite
|
Sign up to set email alerts
|

Fuelwood scarcity, energy substitution, and rural livelihoods in Namibia

Abstract: ABSTRACT. In Namibia, as in many parts of Africa, households are highly dependent on forest resources for their livelihoods, including energy needs. Using data originally collected for Namibia's forest resource accounts and insights from a non-separable household model, this paper estimates household fuelwood demand. Specifically, the factors underlying the substitution between fuelwood collected from open access forest resources, cow dung, and fuelwood purchased from the market are analysed. Heckman two-step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…According to Brouwer et al (1997), the switch was caused by increase in distance to fuel collection points as fuelwood becomes scarce. On the contrary, Palmer and Macgregor (2009) found very little evidence for substitution between fuelwood and dung; rather the use of cow dung as fuel was a predominant feature in livestock rearing communities. However, the livestock rearing regions also generally experienced acute fuelwood scarcity, hence it was possible that reliance on dung was an adaptive response to fuelwood scarcity.…”
Section: Hypothesis 1 Influence Of Energy Access On Dietary Choices mentioning
confidence: 85%
See 1 more Smart Citation
“…According to Brouwer et al (1997), the switch was caused by increase in distance to fuel collection points as fuelwood becomes scarce. On the contrary, Palmer and Macgregor (2009) found very little evidence for substitution between fuelwood and dung; rather the use of cow dung as fuel was a predominant feature in livestock rearing communities. However, the livestock rearing regions also generally experienced acute fuelwood scarcity, hence it was possible that reliance on dung was an adaptive response to fuelwood scarcity.…”
Section: Hypothesis 1 Influence Of Energy Access On Dietary Choices mentioning
confidence: 85%
“…The results are therefore mixed, with some authors suggesting that fuelwood scarcity would lead to use of dung as fuel (Dewees 1989;Brouwer et al 1997;and Palmer and Macgregor 2009), while others (Mekonnen 1999) found other reasons that motivated the use of dung as fuel. The energy ladder model has been disproved in several settings.…”
Section: Hypothesis 1 Influence Of Energy Access On Dietary Choices mentioning
confidence: 99%
“…A study in Ethiopia shows that rural households in forest-degraded areas increase their labour input for collection in response to a shortage in fuelwood (Damte et al, 2012). A Namibian study on fuelwood scarcity also confirmed more labour going into wood collection rather than reduced energy consumption (Palmer & MacGregor, 2008). These studies found limited evidence for energy substitution away from fuelwood to other energy sources, despite the declining availability of forest and non-forest stocks.…”
Section: The Traditional Rural African Village Energy Contextmentioning
confidence: 98%
“…Fuelwood deficits are becoming an increasing problem in rural parts of Africa, adding to the wood collection burden on rural households. In many parts of Africa, households are highly vulnerable to the rapidly degrading forest resources (Palmer & MacGregor, 2008). The reason is that fuelwood is collected primarily from natural wood-land and shrub-land, which are non-forest-type sustainable sources (Aron et al, 1991).…”
Section: The Traditional Rural African Village Energy Contextmentioning
confidence: 99%
“…4). But the dominant biomass fuel was leaves and twigs.Firewood is found always preferable to the households, but most of the rural households are not able to buy firewood with comparatively higher cost than the other biomass (cowdung, leaves and twigs, branches, bamboo, rice straw and rice husk -Arnold et al , Jashimuddin et al 2006, Palmer & Macgregor 2009). Furthermore, women and children can collect those free of cost from their homestead, agricultural land and also from the neighbors (pers.…”
mentioning
confidence: 99%